Multicriteria decision aid for agile methods evaluation using fuzzy PROMETHEE. Issue 12 (11th September 2018) - El Beggar, Omar
Abstract: The last decade is marked by the blossom of agile methods and their growing use in many IT projects. They shared common principles and values, such as customer collaboration, early and continuous delivery of releases, accept requirements changing, and other common principles advocated by the agile manifesto since 2001. Meanwhile, there are significant differences among the practices adopted by the agile methods to fulfill agility's principles and values. The differences could be interpreted in terms of how an agile method judges the relative importance of such principles or its orientation to a specific project viewpoint (organizational, technical, or conceptual) rather than others. This fact leads to a necessity of a deep evaluation of agile methods to choose the best‐fit method suited for a project. Moreover, vague and uncertain information used to evaluate those lightweight methodologies could represent an additional difficulty for decision makers (DM). To drawback this problem, the multiple criteria decision aid (MCDA) method fuzzy PROMETHEE is proposed to assess agile methods with regard to different conflicting criteria and handling besides uncertainty in decision making. Furthermore, a sensitivity analysis is provided to validate results and verify their stability.